2006
DOI: 10.1175/jcli3658.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Global Vegetation–Climate Feedbacks from Observations*

Abstract: The feedback between global vegetation greenness and surface air temperature and precipitation is assessed using remote sensing observations of monthly fraction of photosynthetically active radiation (FPAR) for 1982 to 2000 with a 2.5° grid resolution. Lead/lag correlations are used to infer vegetation–climate interactions. Furthermore, a statistical method is used to quantify the efficiency of vegetation feedback on climate in the observations. This feedback analysis provides a first quantitative assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
145
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(152 citation statements)
references
References 50 publications
5
145
1
1
Order By: Relevance
“…Moreover, comparison of present-day climate simulations with satellitederived information could be helpful (Wang et al, 2005a). Based on the statistical analysis of remote sensing observations, for example, Liu et al (2006a) suggest strong positive boreal vegetation-temperature feedback.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Moreover, comparison of present-day climate simulations with satellitederived information could be helpful (Wang et al, 2005a). Based on the statistical analysis of remote sensing observations, for example, Liu et al (2006a) suggest strong positive boreal vegetation-temperature feedback.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…It strongly influences the exchange of energy, substances and moisture between land and atmosphere through photosynthesis, respiration and transpiration (Graetz, 1991;Mcpherson, 2007). At the same time, the vegetation growth condition is largely affected by climate factors, such as precipitation, air temperature and greenhouse gases (Füssler and Gassmann, 2000;Lotsch et al, 2003;Liu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, human-induced land cover changes were the main human activities in our research period since no other drastic human activities were found in the DRB [4,16,17]. Although the spatial distribution of land cover is dominantly controlled by climate on a global scale [41][42][43], recent studies concluded that regional land cover change has been mainly changed by humans [44][45][46].Our results support that human actions are the main factor altering the land cover changes in the DRB through analyzing differences between satellite LAI and simulated LAI from Biome-BGC model. Deforestation was confirmed as the main land cover change in the DRB [16,17,19].…”
Section: Changes Of Land Cover Changes and Their Impactsmentioning
confidence: 93%
“…Deforestation was confirmed as the main land cover change in the DRB [16,17,19]. On the other hand, potential LAI without impacts of human activities indicated that forests would have flourished more due to the increased rainfall [42,43]. From the view of different seasons, changes of the human-induced land cover in the dry season are strongest because it is the best season of logging in the DRB.…”
Section: Changes Of Land Cover Changes and Their Impactsmentioning
confidence: 99%